(untitled) (Emergency Care Journal, 2026)
Tetanus is a life-threatening, preventable infection caused by the neurotoxin of Clostridium tetani. Despite global vaccination initiatives, cases of adult and maternal tetanus still occur even in individuals with prior immunization. A 21-year-old female presented 15 days after a spontaneous home abortion with fever, trismus, neck stiffness, generalized rigidity, and stimulus-induced spasms. She had received the complete tetanus vaccination. Examination revealed risus sardonicus, opisthotonus, and autonomic instability. Laboratory investigations revealed mild anemia and elevated liver enzymes, and protective anti-tetanus IgG levels, while neuroimaging, abdominal imaging, and cultures were unremarkable. She received human tetanus immunoglobulin, antibiotics, benzodiazepines, magnesium sulfate, baclofen, and intensive supportive care, including mechanical ventilation and vasopressors. Despite intensive care unit care, the patient’s condition worsened, resulting in death on day 10. Tetanospasmin irreversibly blocks inhibitory neurons, causing uncontrolled muscle spasms and autonomic dysfunction. Diagnosis is clinical; laboratory tests are often non-contributory. Management focuses on neutralizing circulating toxin, preventing bacterial proliferation, controlling spasms, and providing intensive supportive care. Even with intensive management, mortality remains high, primarily due to respiratory failure and autonomic dysfunction. Maternal generalized tetanus may occur following spontaneous abortion outside a healthcare setting, even in previously vaccinated individuals with protective antibody levels, and carries a high risk of mortality.